Butyrate in Energy Metabolism: There Is Still More to Learn - Zhang, Lin; Liu, Chudan; Jiang, Qingyan; Yin, Yulong (Trends in endocrinology and metabolism, 2021)
Butyrate, a main product of gut microbial fermentation, has been recognized as an important mediator of gut microbiota regulation in whole body energy homeostasis. However, the mechanisms of butyrate metabolic control remain unclear. This review summarizes studies that directly examined the effects of butyrate on metabolic health. The effects of butyrate on metabolic functions, including thermogenesis, lipid and glucose metabolism, appetite, inflammation, and influence on gut microbiota, are described. The effects of butyrate on cellular systems via G protein-coupled receptors (GPRs), as a histone deacetylase inhibitor, and as a substrate that is metabolized intercellularly, are also discussed. Hopefully, a better understanding of butyrate metabolic regulation may provide new perspectives for the nutritional prevention and treatment of metabolic diseases. Butyrate is a vital mediator between gut microbiota and host metabolic health.Butyrate has regulatory effects on body weight, body composition, and glucose homeostasis.Butyrate is absorbed and metabolized by tissues and cells beyond the colon and has regulatory effects on their metabolic functions.The metabolic effects of butyrate are subject to multiple regulatory mechanisms.